Mała ojczyzna ponad granicą? Cienie przeszłości, wspólne inicjatywy kulturalne i edukacyjne oraz plany na przyszłość w polskim Zgorzelcu i niemieckim Gorlitz = Local homeland Beyond borders? The shadows of the past, common cultural and educational initiatives as well as future plans in Polish Zgorzelec and German Gorlitz - Ruhland, Katarzyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Since 1945 the left and right bank parts of Zgorzelec began to form separate history. Practically speaking for many years the border was the only shared element and created a serious obstacle to the development of both German Gorlitz as well as Polish Zgorzelec.
Keywords: Zgorzelec; Göritz; mała ojczyzna; współpraca polsko-niemiecka; pogranicze polsko-niemieckie